On the Relationship between Social Support and Early Breastfeeding Termination - Marzieh Faghani Aghoozi; Mohaddeseh Karimi Khoshal; Sanaz Faiazi; Shahnaz Tork Zahrani; Malihe Amerian (Zanjan University of Medical Sciences and Health Services, 2020)
Background: There is no substitute to mother breastfeeding; on the one hand, mothers need all-out support, especially in the first days after delivery, which is one of the effective factors for women's success in breastfeeding. Objectives: The aim of this study is to investigate the relationship between social support and early termination of breastfeeding. Methods: This retrospective study examined the degree of social support for mothers embarking on early termination of breastfeeding. It covered a group of 235 individuals (150 individuals in the control group and 85 in the experimental group) as its participants. The data were collected through three separate questionnaires: The Multidimensional Scale of Perceived Social Support Questionnaire, the demographic questionnaire and the researcher-made questionnaire of evaluation of breastfeeding. The T-test, MannWhitney, chi-square and logistic regression tests were used for analysis by SPSS 16. Results: The results revealed that compared to mothers in the experimental group, unwanted pregnancies (p=0.001) and caesarian section deliveries (p=0.007) were significantly more observed in the control group mothers. Those characterized by termination of breastfeeding received (about 22 times) weaker social support compared to the breastfeeding mothers (p<0.001, OR~22). Furthermore, the first breastfeeding upon birth was less (about 0.211 times) observed among the experimental group mothers than the group of mothers characterized by breastfeeding (p=0.006, OR~0.211). Conclusion: Husband encouragement and support and high social support are highly effective in successful breastfeeding and in this line, all-out support for mother, including support by family and society, seem very necessary.